Assessing Volition in Pediatrics: Using the Volitional Questionnaire and the Pediatric Volitional Questionnaire - Anne Kiraly-Alvarez (Open Journal of Occupational Therapy, 2015)
Evidence suggests that pediatric occupational therapists predominantly use bottom-up, impairment-focused theoretical frameworks and assessments to guide their practice, despite the current trends promoting topdown, occupation-based approaches. Understanding a child’s volition, guided by the use of the Model of Human Occupation, contributes to a more occupation-based, client-centered, holistic, and strength-based approach to therapy. Two assessment tools, the Volitional Questionnaire and the Pediatric Volitional Questionnaire, contribute to a therapists’ understanding of children’s volition. These assessments facilitate therapists’ clinical reasoning and the ability to assess and address volition throughout the occupational therapy process.